Ruminai Macro Mineral Solubility of Indigofera zollingeriana Top-Leaves from Plants with Different Planting Density Using In Vitro Technique. Issue 1 (1st April 2022) - Ernawati, A; Abdullah, L
Abstract: Indigofera zollingeriana is a tremendous potential forage plant due to its high nutrient content and potential to be a protein and mineral source in a sustainable system. Mineral fulfillment in ruminants is determined by their bioavailability. This study evaluated the ruminal macro mineral solubility of I. zollingeriana growing with different planting densities. The field experiment was laid out in a randomized block design with three different planting densities, 8000plants/ha, 13333plants/ha, 20000plants/ha, and 3 replicates. An in vitro experiment evaluated macrominerals solubility and incubated in rumen liquor at 0, 3, 6, 12, 24, 48, and 72 h. The results showed that increased planting densities significantly(P<0.05) decreased DM degradability. Planting density also gave various effects on the level of kinetic parameters, effective solubility(ES), and solubility of macro minerals(P<0.05). The plant of 8000 to 13333plants/ha has a higher Ca and Mg solubility, kinetic parameters, and ES of macro minerals compared to the density of 20000plants/ha. Based on these results, it can be concluded that higher bioavailability of macro minerals is obtained from populations of 8000 to 13333plants/ha, so that the planting of I. zollingeriana needs to be carried out with a population of 8000 to 13333plants/ha to produce forage macro mineral biomass and can be utilized by livestock optimally.